The Effect of Concurrent Training on Serum Androgens Levels and Sexual Function in Menopausal Women - Mohammad Parastesh; Zahra Mohseni; Esfandiar Khosravi Zadeh; Abbas Saremi (Hamadan University of Medical Sciences, 2021)
Background and Objective: Women's sexual function decreases during menopause, which in turn reduces their quality of life. Some studies have suggested that physical activity is associated with increased serum levels of androgens and improved sexual function. The aim of this study was to investigate the effect of concurrent training on serum androgens levels and sexual function in postmenopausal women. Material and Methods: The study was performed quasi-experimentally. The statistical sample of this study consisted of 30 postmenopausal women with an average weight of 65.1±5.4kg. Subjects were randomly divided into two groups of simultaneous training and control. The training group performed 8 weeks of concurrent training. Serum levels of dehydroepiandrosterone, testosterone and sexual function were measured 48 hours before and after training. Data were analyzed using SPSS 23 statistical software at a significance level of 0.05. Results: Concurrent training in the experimental group significantly increased serum testosterone levels compared to the control group (P=0.042). Although concurrent training increased the serum level of dehydroepiandrosterone in the experimental group, but this value was not significant (P=0.396). Concurrent training also increased sexual function in the areas of desire (P=0.035), marital satisfaction (P=0.002) and total scores (P=0.047) in the concurrent training group compared to the control group. Conclusion: In general, based on our findings, it seems that concurrent training improves sexual function in postmenopausal women by increasing serum testosterone levels.